Effects of green decorated AgNPs on lignin-modified magnetic nanoparticles mediated by Cydonia on cecal ligation and puncture-induced sepsis - Zhou Lei; Yao Yanfen; Wang Quanzhen; Wang Peng; Hong Shan; Kong Li (Open Chemistry, 2023)
Sepsis is a common and deadly syndrome that despite all the progress in its control, the death rate caused by it is high. Sepsis is a serious problem that needs immediate attention and treatment. This infection, especially if it is caused by bacteria resistant to several drugs, causes high mortality. About two-thirds of sepsis cases occur in hospitalized patients. Several factors such as increasing the age of the population, increasing the duration of chronic diseases, high consumption of antibiotics and corticosteroids, use of mechanical devices and intravascular devices play a role in increasing its incidence. We herein demonstrate the biogenic procedure for the in situ immobilizing gold nanoparticles over lignin (Lig)-modified Fe3O4 magnetic nanoparticles mediated by Cydonia leaf extract (Fe3O4@Lig-Ag NPs) and its catalytic activity on the acetylation of alcohols using acetic anhydride and subsequent biological performances. The successful synthesis of Fe3O4@Lig-Ag NPs was assessed using an array of advanced techniques like field emission scanning electron microscopy, fourier transformed infrared spectroscopy, transmission electron microscopy EDX, elemental mapping, vibrating-sample magnetometer, and X-ray diffraction. Cecal ligation and puncture was used for inducing the sepsis model in rats. Several doses of Fe3O4@Lig-Ag NPs (45, 15, and 5 µg/kg) on oxidant–antioxidant, inflammatory mediators mRNA such as IL-1 and TNF-α, and its effects on the levels of expression were assessed in the kidney, liver, duodenum, lung, and stomach. When septic rats kidney, liver, duodenum, lung, and stomach were compared with those of the control group, it was found that Fe3O4@Lig-Ag NPs dose-dependent administration raised glutathione levels and superoxide dismutase activity and significantly reduced the levels of malondialdehyde. The Fe3O4@Lig-Ag NPs (45 µg/kg) indicated greater anti-oxidative effects than the 5 and 15 µg/kg doses for all the assessed parameters. In addition, the expression of TNF-α mRNA in the CLP + 45 µg/kg group was decreased in comparison with the control group. Fe3O4@Lig-Ag NPs reduced oxidative stress by enhancing the free radicals scavenging effects and supporting endogenous antioxidants. The Fe3O4@Lig-Ag NPs potent antioxidant property may be related to the cytokine cascade suppression during sepsis. The above findings offer that Fe3O4@Lig-Ag NPs administration may indicate a modern treatment for the inhibition of liver, kidney, lung, duodenum, and stomach tissues damage caused by septic conditions.